Interactions between whale sharks, Rhincodon typus Smith, 1928 (Orectolobiformes, Rhincodontidae), and Brazilian fisheries: The need for effective conservation measures - Vargas Barbosa-Filho, Marcio Luiz; Tavares, Davi Castro; Siciliano, Salvatore; Moura, Jailson Fulgencio de; Costa-Neto, Eraldo Medeiros; Motta, Fabio dos Santos [UNESP]; Koike, Christine Del Vechio (Elsevier B.V., 2016)
This study reports three interaction events between the whale shark (Rhincodon typus) and fisheries in Brazilian waters. Two events were described as incidental captures in a gillnet fishery on the northern coast of Rio de Janeiro State, in southeastern Brazil. The last event took place at the Royal Charlotte Oceanic Bank (RCOB), in the southern region of Bahia State, where five fishermen filmed their interaction with a juvenile specimen. For one of the incidental captures, the fish was landed and consumed by locals, and for the other, the shark was released. In the RCOB, the fishermen touched the whale shark with their hands, wooden sticks and even rode on it. In addition, 74 interviews were conducted with fishermen from Bahia about sightings and possible interactions with R. typus. According to statements made by the fishermen, although not frequent, the conduct reported for the RCOB occasionally takes place in the region. Evaluating information of this nature is important to support government plans that regulate fishing activities in order to reduce incidental captures and the harassment of whale sharks. Encouraging the participation of fishermen in a collaborative monitoring program for R. typus may be a good way to better understand the threats to the species at a reduced cost, particularly for developing countries, such as Brazil. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Artisanal fisheries; Endangered species; Collaborative monitoring program